2011
DOI: 10.1038/gene.2011.40
|View full text |Cite
|
Sign up to set email alerts
|

Pathway-based analysis of genetic susceptibility to cervical cancer in situ: HLA-DPB1 affects risk in Swedish women

Abstract: We have conducted a pathway-based analysis of genome-wide single-nucleotide polymorphism (SNP) data in order to identify genetic susceptibility factors for cervical cancer in situ. Genotypes derived from Affymetrix 500k or 5.0 arrays for 1076 cases and 1426 controls were analyzed for association, and pathways with enriched signals were identified using the SNP ratio test. The most strongly associated KEGG (Kyoto Encyclopedia of Genes and Genomes) pathways were Asthma (empirical P ¼ 0.03), Folate biosynthesis (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
20
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(21 citation statements)
references
References 53 publications
1
20
0
Order By: Relevance
“…Another cervical cancer GWAS performed in China also found associations with the HLA-DPB1 and HLA-DPB2 genes (42). Further support for a role for HLA molecules as modulators of susceptibility to cervical cancer comes from a pathway analysis performed on the cervical cancer GWAS, in which a subset was used as replication cohort in this study and identified several pathways, including HLA genes, that influence risk of cervical cancer (26). However, in the oropharyngeal cancer GWAS, the pathways and SNPs associated with HLA molecules were not highly ranked, with the most significant SNP P value equal to 1 × 10 −2 .…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…Another cervical cancer GWAS performed in China also found associations with the HLA-DPB1 and HLA-DPB2 genes (42). Further support for a role for HLA molecules as modulators of susceptibility to cervical cancer comes from a pathway analysis performed on the cervical cancer GWAS, in which a subset was used as replication cohort in this study and identified several pathways, including HLA genes, that influence risk of cervical cancer (26). However, in the oropharyngeal cancer GWAS, the pathways and SNPs associated with HLA molecules were not highly ranked, with the most significant SNP P value equal to 1 × 10 −2 .…”
Section: Discussionmentioning
confidence: 98%
“…The details of population and QC have been described by Ivansson and colleagues (26). The data we received included for each SNP, the SNP identifier, the genomic location, and the P value from the association analysis that was estimated by ORs and 95% CI using multivariable unconditional logistic regression assuming a log-additive genetic model.…”
Section: Methodsmentioning
confidence: 99%
“…However, 50%–90% of early cervical intraepithelial neoplasia (CIN) cases regress spontaneously [2, 3], suggesting a genetic influence. Previous evidence for host genetic factors contributing to susceptibility to cervical intraepithelial neoplasia (CIN) and invasive cervical cancer (ICC) has come from family-based and case-control studies [48]. …”
Section: Introductionmentioning
confidence: 99%
“…711 A growing body of literature also highlights the important role of immunogenetics in HPV-related carcinogenesis. 1215 …”
Section: Introductionmentioning
confidence: 99%